Manual de procedimientos administrativos para el mejoramiento de las buenas prácticas de higiene en el matadero municipal del cantón Bolívar - Carranza García, Renato Adrián (2012)
The objective was to develop an Administrative Procedures Manual to improve the Good Hygienic Practice in Bolivar Canton Municipal Slaughterhouse. For this purpose, we performed an analysis of the functioning of the municipal slaughterhouse, based on existing Stockyards Act, to check the current status of the abattoir were surveyed the community in which it is located, and an interview with manager the results institution. Los initial diagnosis, compared to the checklist, infrastructure, facilities and equipment determined compliance of 25% compared to 75% failure: for slaughterhouse staff observed a 91% non-compliance on tasks. Then was made the administrative procedures manual which will serve to guide you through each of the activities related to improving hygiene practices. The application of this manual will contribute to the process of improving the standard of cleaning and disinfection of equipment and utensils, control of personal hygiene, proper handling of chemicals, control of suppliers, integrated pest management, staff training and good facilities Slaughterhouse. Finally, we conducted a socialization of the Procedural Manual for staff and administrative processes of the Slaughterhouse and the Association of the Canton of meat retailers Bolivar, with the sole purpose of publicizing the benefits that would apply if the activities of this document.